Bonding material and bonded structure

By using a bonding material containing silver nanoparticles and eutectic low-melting alloy particles in printable electronic technology, a high melting point intermetallic compound is formed, which solves the problem of insufficient heat resistance of the PET film substrate and achieves high resistance at low temperatures Thermal bonding effect.

CN119255876APending Publication Date: 2025-01-03PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380044650.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-23
Filing Date
2023-05-22
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In printable electronic technology, due to the low glass transition temperature of the PET film substrate, the lead-free solder used during bonding is insufficient heat resistance, and the low melting point solder is easily remelted after the temperature rises, which cannot meet the high heat resistance Require.

Method used

Using a bonding material containing silver nanoparticles and eutectic low-melting alloy particles, the eutectic low-melting alloy particles solidifies between silver nanoparticles by heating to form intermetallic compounds with high melting points, and is composed of elements such as Cu, Sn, and In. The intermetallic compounds are linked to provide high heat resistance.

Benefits of technology

The bonding materials and bonding structures with high heat resistance are formed under low temperature and short heating, which avoids remelting and improves the stability of the bonded device at high temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119255876A_ABST
    Figure CN119255876A_ABST
Patent Text Reader

Abstract

The bonding material comprises: a solder alloy having a median particle diameter (D50) of 100-2000 nm, comprising Sn, Bi, In, and other unavoidable components, and having a melting point of 100 DEG C or less; metal nanoparticles, which are Cu nanoparticles having a median diameter (D50) of 50 nm to 500 nm; and a flux, the metal nanoparticles have, on the surface thereof, a protective film that is detached at a temperature higher than the melting point of the solder alloy and lower than 100 DEG C, and the weight ratio of the solder alloy to the metal nanoparticles is the ratio at which all of Sn and In contained in the solder alloy are intermetallic compounds with the metal nanoparticles in an equilibrium state diagram.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a bonding material and a bonding structure for bonding two members using a metal material, which are used in fields such as printable electronic technology. Background Art

[0002] Devices used in the field of printable electronics and the like include a device having a joined structure in which two members, a substrate having a circuit and a film-like resin as a base material, and an electronic component are joined together for the purpose of imparting flexibility.

[0003] As the film-shaped resin for the purpose of imparting flexibility, various resins such as polyethylene terephthalate (PET), polyamide, and polyimide are used, and it is desirable to use a PET film in view of the price.

[0004] Since the glass transition temperature of the PET film is low, there is a problem that the PET film cannot withstand the soldering temperature when a common lead-free solder (for example, Sn-3.5Ag-0.5Cu, melting point: 219° C.) is used when joining electronic components to a substrate.

[0005] Therefore, when a PET film substrate is used, it is necessary to use a silver paste obtained by adding particulate silver to a thermosetting resin or a low-melting-point lead-free solder as a bonding material for electronic components for bonding.

[0006] However, in the case of silver paste, since bonding is performed by curing of a thermosetting resin, when used in a PET film substrate having low heat resistance, a resin having a low curing temperature must be used. On the other hand, when a lead-free solder having a low melting point is used for bonding, since the melting point is also low, remelting occurs when the temperature rises above the melting point after bonding. Therefore, in either case, there is a problem of low heat resistance after bonding.

[0007] Therefore, there is a demand for a joining material and a joined structure having the characteristics of low temperature during joining and excellent heat resistance after joining.

[0008] As a solution to this problem, a bonding material has been proposed, which is a bonding material comprising silver nanoparticles of nano-sized silver and eutectic low-melting-point alloy particles, wherein the silver nanoparticles are annealed by heating, and the molten eutectic low-melting-point alloy particles flow into the spaces between the annealed silver nanoparticles to fill them and solidify, thereby forming a bond (see, for example, Patent Document 1).

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2018-137213 Summary of the invention

[0012] A bonding material in one embodiment of the present application includes: a solder alloy, wherein the median particle size D50 is 100nm to 2000nm, composed of Sn, Bi, In and other inevitable components, and having a melting point below 100°C; metal nanoparticles, which are Cu nanoparticles with a median particle size D50 of 50nm to 500nm; and a flux component, wherein the metal nanoparticles have a protective film on their surface that detaches at a temperature higher than the melting point of the solder alloy and lower than 100°C, and the weight ratio of the solder alloy to the metal nanoparticles is a ratio in which all Sn and In contained in the solder alloy become intermetallic compounds with the metal nanoparticles in the equilibrium diagram.

[0013] In addition, a bonding structure of one embodiment of the present application comprises an electronic component having a first electrode, a circuit substrate having a second electrode, and a bonding layer between the first electrode and the second electrode, wherein the first electrode and the second electrode are bonded by the bonding layer, and the bonding layer connects the first electrode and the second electrode by using an intermetallic compound composed of two or more elements of Cu, Sn, and In, and has a Bi-containing portion in the form of an island in a matrix of the intermetallic compound. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a schematic diagram which shows the structure of the bonding material of this Embodiment 1.

[0015] Figure 2 It is a schematic diagram showing the structure of the joined structure according to the first embodiment.

[0016] Figure 3 This is a diagram showing Table 1 showing components contained in the bonding materials of Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-12, particle sizes, weight ratios, and evaluation results.

[0017] Figure 4 This is a diagram showing Table 2 showing the conditions and evaluation results of the bonding materials of Examples 2-1 to 2-10 and Comparative Examples 2-1 to 2-6. DETAILED DESCRIPTION

[0018] In the bonding material described in Patent Document 1, since the eutectic low melting point alloy remains after bonding even under short-time heating, there is a problem of remelting when the temperature rises above the melting point after bonding. In addition, in order to ensure heat resistance, long-time annealing is required for sintering of silver nanoparticles, which increases the thermal damage to the resin substrate, which becomes a problem in resin substrates with low heat resistance.

[0019] The present application is an invention for solving the conventional problems, and an object of the present application is to provide a joining material and a joining structure that can exhibit high heat resistance under heating at a low temperature and for a short time.

[0020] The first method of bonding materials includes: a solder alloy, wherein the median particle size D50 is 100nm to 2000nm, composed of Sn, Bi, In and other inevitable components, and having a melting point below 100°C; metal nanoparticles, which are Cu nanoparticles with a median particle size D50 of 50nm to 500nm; and a flux, wherein the metal nanoparticles have a protective film on their surface that detaches at a temperature higher than the melting point of the solder alloy and lower than 100°C, and the weight ratio of the solder alloy to the metal nanoparticles is a ratio in which all Sn and In contained in the solder alloy become intermetallic compounds with the metal nanoparticles in the equilibrium diagram.

[0021] A second aspect of the bonding material may be that in the first aspect, the solder alloy has a composition of Sn-55wt.%Bi-20wt.%In.

[0022] A third aspect of the bonding material may be the bonding material according to the first or second aspect, wherein a weight ratio of the metal nanoparticles to a total of the solder alloy and the metal nanoparticles is 30 to 50 wt.%.

[0023] A fourth aspect of the bonding material may be the bonding material according to the first or second aspect, wherein a weight ratio of the metal nanoparticles to a total of the solder alloy and the metal nanoparticles is 37.5 to 50 wt. %.

[0024] A fifth aspect of the bonding material may be that in the first or second aspect, a weight ratio of the metal nanoparticles to the total of the solder alloy and the metal nanoparticles is 40 to 50 wt.%.

[0025] A sixth aspect of the bonding material may be any one of the first to fifth aspects, wherein the protective film is a linear carboxylic acid having 4 to 8 carbon atoms.

[0026] The seventh mode of the bonding structure comprises an electronic component having a first electrode, a circuit substrate having a second electrode, and a bonding layer between the first electrode and the second electrode, wherein the first electrode and the second electrode are bonded by the bonding layer, and the bonding layer is connected between the first electrode and the second electrode by using an intermetallic compound composed of two or more elements of Cu, Sn, and In, and has a Bi-containing portion in the form of an island in a matrix of the intermetallic compound.

[0027] According to the bonding material of the present application, a bonding material and a bonding structure can be provided which can rapidly form a high melting point intermetallic compound between the solder alloy and metal nanoparticles after the solder alloy is melted and exhibit high heat resistance under low temperature and short time heating.

[0028] Hereinafter, a joining material and a joining structure according to an embodiment of the present application will be described in detail with reference to the drawings.

[0029] (Implementation method 1)

[0030] <Joining materials>

[0031] Figure 1 It is a schematic diagram which shows the structure of the bonding material of this Embodiment 1.

[0032] The bonding material 101 of the present embodiment 1 includes a solder alloy 102, metal nanoparticles 103, and a flux 105. The solder alloy 102 has a median particle size D50 of 100 nm to 2000 nm, is composed of Sn, Bi, In and other inevitable components, and has a melting point of 100°C or less. The metal nanoparticles 103 are Cu nanoparticles having a median particle size D50 of 50 to 500 nm. In addition, the metal nanoparticles 103 have a protective film 104 on their surface that is detached at a temperature higher than the melting point of the solder alloy 102 and lower than 100°C. In addition, the weight ratio of the solder alloy 102 to the metal nanoparticles 103 is composed of a ratio in which all Sn and In contained in the solder alloy become compounds with the metal nanoparticles 103 in the equilibrium diagram.

[0033] Therefore, the bonded portion bonded by using the bonding material does not remelt at 100° C. or lower. Therefore, even if the operating temperature of the device after bonding is 100° C. or higher, high heat resistance can be exhibited without melting.

[0034] <Joint structure>

[0035] Figure 2 It is a schematic diagram showing the structure of the joined structure according to the first embodiment.

[0036] The bonding structure 106 bonded by the bonding material 101 of the first embodiment includes an electronic component 108 having a first electrode 107, a circuit substrate 110 having a second electrode 109, and a bonding layer 111 between the first electrode and the second electrode. The first electrode 107 and the second electrode 109 are bonded by the bonding layer 111. The bonding layer 111 is connected (filled) between the first electrode 107 and the second electrode 109 by an intermetallic compound 112 composed of two or more elements of Cu, Sn, and In, and has an island-shaped Bi-containing portion 113 in the matrix of the intermetallic compound composed of two or more elements of Cu, Sn, and In. It should be noted that the Bi-containing portion 113 is substantially composed of only Bi, although it contains trace amounts of other components below the solid solubility limit.

[0037] Here, the state of being connected (filled) refers to a state in which the first electrode 107 and the second electrode 109 are connected by the intermetallic compound. In addition, the so-called "island shape" refers to a state in which all the Bi-containing portions 113 are not connected between the first electrode 107 and the second electrode 109, but are dispersed between the intermetallic compounds.

[0038] Therefore, even if the temperature of the bonding structure 106 rises to or above the melting point of the bonding material 101 during operation of the device having the bonding structure 106, remelting does not occur because there is no molten component in the bonding layer 111. Thus, high heat resistance above the bonding temperature can be achieved.

[0039] Hereinafter, each member constituting the joining material and the joined structure will be described.

[0040] <Solder alloy>

[0041] The solder alloy 102 becomes a liquid phase component in the joining process, reacts with the metal nanoparticles 103 to form a high melting point intermetallic compound. In addition, the solder alloy 102 is composed of Sn, Bi, In and other inevitable components, and is a solder alloy with a melting point of 100°C or less. As a result, joining at a low temperature of 100°C can be achieved. In addition, since Sn and In can form a high melting point intermetallic compound with Cu of the metal nanoparticles 103 described later, and the melting point of Bi is as high as 272°C, it can show high heat resistance that does not melt even at 100°C or above.

[0042] It should be noted that the above-mentioned intermetallic compound is an intermetallic compound composed of two or more elements among Cu, Sn, and In.

[0043] The solder alloy 102 has a median particle size D50 of 100 to 2000 nm, which has a large specific surface area and is close to the particle size of the metal nanoparticles 103, thereby forming an intermetallic compound in a short time and preventing the generation of pores generated during the reaction between the liquid phase and the solid phase.

[0044] <Metal Nanoparticles>

[0045] The metal nanoparticles 103 react with Sn and In contained in the solder alloy 102 melted in the joining process to form an intermetallic compound. The median particle size D50 of the metal nanoparticles 103 is 50 to 500 nm. Thus, a high melting point intermetallic compound can be formed in a short time in the joining process while suppressing the aggregation in the joining material 101.

[0046] The metal nanoparticles 103 are Cu nanoparticles, which can react with Sn and In contained in the solder alloy 102 to form a high melting point intermetallic compound.

[0047] The metal nanoparticles 103 have a protective film 104 described later on the surface. This can suppress surface oxidation even in metal nanoparticles having a small particle size.

[0048] <Protective film>

[0049] The protective film 104 is detached from the surface of the metal nanoparticle 103 at a temperature above the melting point of the solder alloy 102 and below 100°C. By having such a protective film 104, it is possible to suppress the surface oxidation of the metal nanoparticle 103 until the solder alloy 102 melts. In addition, after the solder alloy 102 melts, the protective film 104 is detached, and thus the metal nanoparticle 103 contacts the molten solder alloy 102 in a state where there is a very small amount of oxide film on the surface. As a result, the formation of the intermetallic compound between the metal nanoparticle 103 and the solder alloy proceeds rapidly, and it is possible to achieve excellent heat-resistant bonding under low temperature and short time conditions.

[0050] The protective film 104 has no problem as long as it is a film that is detached from the surface of the metal nanoparticle 103 at a temperature above the melting point of the solder alloy 102 and below 100°C, but it is particularly desirable that the protective film is a straight-chain carboxylic acid having 4 to 8 carbon atoms. These components have a carboxyl group and detach from the surface of the metal nanoparticle 103 at a temperature above the melting point of the solder alloy 102 and below 100°C. It is believed that the oxidation of the surface of the metal nanoparticle 103 is suppressed, and it is rapidly detached at 100°C, and it helps to remove the surface oxide of the solder alloy 102 as an active agent component. Therefore, it is possible to achieve excellent heat resistance bonding under conditions of lower temperature and shorter time.

[0051] <Flux>

[0052] The flux 105 is contained in order to exhibit the paste characteristics for removing the oxide film existing on the surface of the solder alloy 102, suppressing the reoxidation of the metal nanoparticles 103, and supplying the material in the coating process and the like during the bonding process. The flux 105 facilitates the melting of the solder alloy 102 and the diffusion of the metal elements between the melted solder alloy 102 and the surfaces of the metal nanoparticles 103. The flux 105 only needs to contain a component for removing the oxide film existing on the surface of the solder alloy 102 and a solvent having a boiling point higher than the melting point of the solder alloy 102 in order to prevent reoxidation during the bonding process.

[0053] (Example)

[0054] In order to confirm the effect of the present embodiment 1, as Examples 1-1 to 1-13 and Comparative Examples 1-1 to 1-5, bonding materials 101 were prepared in which the particle sizes, mixing ratios, and types of protective films 104 of solder alloys 102 and metal nanoparticles 103 were changed. The components contained in the bonding materials 101 in Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-12 and their weight ratios, the particle sizes of the solder alloys 102 and metal nanoparticles 103, and the evaluation results are shown in FIG. Figure 3 Table 1. The particle sizes of the solder alloy 102 and the metal nanoparticles 103 shown in Table 1 are all median particle sizes D50.

[0055] <Joining Materials 101>

[0056] As the solder alloy 102 of the first embodiment, Sn-55 wt. % Bi-20 wt. % In was evaluated. Also, as the metal nanoparticles, Cu nanoparticles were evaluated.

[0057] The bonding material 101 is produced as follows.

[0058] (1) First, the metal nanoparticles 103 are weighed to a desired amount, and the surface thereof is covered with the protective film 104 .

[0059] (2) Then, the solder alloy 102 is weighed and added, and mechanically kneaded to mix uniformly.

[0060] (3) Thereafter, the flux 105 is weighed and added, and kneaded using a twin-shaft planetary kneading machine, thereby obtaining the bonding material 101 .

[0061] <Joining process>

[0062] The bonded structure 106 was produced in order to confirm the effects of the present embodiment 1. The bonding process is as follows.

[0063] First, bonding is performed using the prepared bonding material 101 .

[0064] (a) A bonding material 101 is supplied onto a Cu plate using a metal mask having a thickness of 100 μm and an opening of 1 mm×1 mm.

[0065] (b) A Si element is mounted on the supplied bonding material 101. The electrodes of the Si element bonded with the bonding material 101 are formed by plating with Ti / Ni / Au from the Si side.

[0066] (c) A load of 1 MPa was applied to the mounted Si element, and heating was performed at 100° C. for 10 minutes in a N 2 atmosphere to produce a bonded structure 106 in which the electrode of the Si element and the Cu plate were bonded using the bonding material 101 .

[0067] <Evaluation of protective film detachment>

[0068] The results of the evaluation for confirming the effect of the present embodiment 1 are also shown in Figure 3 In Table 1.

[0069] The metal nanoparticles 103 whose surfaces were coated with the protective film 104 were evaluated by differential thermal and thermogravimetric simultaneous measurement (TG / DTA). In Table 1, when a weight loss accompanied by heat of reaction was observed at a temperature above the melting point (solidus temperature 78° C.) of the solder alloy and below 100° C. in TG / DTA, it was considered that the protective film 104 had been detached and was judged as "A", and when it was not observed, it was judged as "C".

[0070] <Joint evaluation>

[0071] After a series of bonding processes, it was confirmed whether the electrodes of the Cu plate and the Si element were bonded. In Table 1, the case of bonding was judged as "A", and the case of non-bonding was judged as "C".

[0072] <Heat resistance evaluation>

[0073] Then, the heat resistance after bonding was evaluated. The bonding material 101 was taken out from the produced bonding structure 106 and evaluated by TG / DTA. In TG / DTA, the case where there was no endothermic behavior at a temperature lower than the melting point of Sn (232°C) was judged as "B", and in particular, the case where there was no endothermic behavior at a temperature lower than the melting point of Bi (271°C) was judged as "A", and the case where endothermic behavior was observed at a temperature lower than the melting point of Sn was judged as "C".

[0074] <Joint status evaluation>

[0075] Next, the bonding state of the bonded structure 106 was evaluated by cross-sectional observation. The produced bonded structure 106 was observed by an electron microscope (SEM), and the case where no abnormality was observed in the formed intermetallic compound 112 was judged as "A", and the case where significant pores existed in the intermetallic compound 112 was judged as "C".

[0076] <Overall Evaluation>

[0077] The case where none of the above evaluation items was "C" was judged as "B", and the case where the heat resistance was "A" was judged as "A", and the case where at least one item was "C" was judged as "C".

[0078] like Figure 3As shown in Table 1, among Examples 1-1 to 1-13, Examples 1-1 to 1-9, 1-12, and 1-13 were all rated "A" in the evaluation of protective film detachment, bonding evaluation, heat resistance evaluation, and bonding state evaluation. Examples 1-10 and 1-11 were rated "A" in the evaluation of protective film detachment, bonding evaluation, and bonding state evaluation, and were rated "B" in the evaluation of heat resistance. All of Examples 1-1 to 1-13 were higher than the evaluation criteria.

[0079] In these examples, when comparing examples 1-1 to 1-4, the particle size of the solder alloy 102 is 100 to 2000 nm. When comparing examples 1-1, 1-5, and 1-6, the particle size of the metal nanoparticles 103 is 50 to 500 nm. In addition, the protective film 104 of examples 1-1 to 1-13 is a straight-chain carboxylic acid having 4 to 8 carbon atoms such as n-butyric acid, hexanoic acid, and octanoic acid. In addition, when comparing examples 1-1, 1-10 to 1-13, the heat resistance is "A" when the weight ratio of the metal nanoparticles is 40 to 50 wt.%, and the heat resistance is "B" when the weight ratio of the metal nanoparticles is 30 to 35 wt.%.

[0080] On the other hand, in Comparative Example 1-1, as a result of cross-sectional observation after joining, pores of several μm were observed in the formed intermetallic compound, and the joining state was evaluated as "C". Although there are still some parts that cannot be fully explained, it can be considered as follows. It can be considered that because the particle size of the solder alloy 102 used in Comparative Example 1-1 is 5000nm, which is larger than the particle size of the metal nanoparticles 103, the intermetallic compound is generated in the surface layer of the solder alloy 102, and the reaction of generating the intermetallic compound does not occur instantly inside the solder alloy 102, but the intermetallic compound is generated by diffusion of elements of the intermetallic compound through the surface layer.

[0081] In Comparative Examples 1-2 and 1-3, the heat resistance was evaluated as "C". This is because solder alloy 102 remains in either case. It is considered that the metal nanoparticles 103 in Comparative Example 1-2 have a large particle size, so they do not fully react to the inside of the metal nanoparticles 103 after joining. It is also considered that the weight ratio of the metal nanoparticles 103 in Comparative Example 1-3 is as small as 25wt.%.

[0082] The change in the solidus temperature caused by the weight ratio of Sn-55wt.%Bi-20wt.%In and Cu was analyzed using a calculated equilibrium state diagram (Thermo-calc). When the weight ratio of Cu as the metal nanoparticle 103 is 25wt.% or less, it can be confirmed to be below 100°C, when it is 30-37.5wt.%, it can be confirmed to be around 232°C, which is the melting point of Sn, and when it is above 40wt.%, it can be confirmed to be around 271°C, which is the melting point of Bi, which is consistent with the above results.

[0083] On the other hand, in Comparative Example 1-4, the bonding evaluation was "C". This is probably because the weight ratio of the metal nanoparticles 103 was as high as 55 wt.%, and the solder alloy 102 did not fully wet and spread when it melted, and the intermetallic compound network was not fully formed.

[0084] In Comparative Example 1-5, lauric acid having a carbon number of 12 was used for the protective film, and no weight loss accompanied by the heat of reaction was observed above the melting point of the solder alloy and below 100°C. In addition, the heat resistance was also "C". This is considered to be because the protective film could not be smoothly detached from the surface of the metal nanoparticle 103 during the bonding process, and the rate of formation of the intermetallic compound on the surface of the metal nanoparticle 103 was low, so the intermetallic compound was not sufficiently formed during the bonding process at 100°C for 10 minutes.

[0085] The following conclusions can be confirmed from the results of the first embodiment.

[0086] In order to demonstrate the effects of the present application, firstly, the particle size of the solder alloy 102 needs to be 100 to 2000 nm.

[0087] Then, the particle diameter of the metal nanoparticles 103 needs to be 50 to 500 nm.

[0088] The weight ratio of the metal nanoparticles needs to be 30 to 50 wt %, and is particularly preferably 40 to 50 wt %. This is because the weight ratio of the solder alloy 102 to the metal nanoparticles 103 is a ratio at which all Sn and In contained in the solder alloy form compounds with the metal nanoparticles 103 in an equilibrium diagram.

[0089] Furthermore, the protective film 104 needs to be detached at a temperature higher than the melting point of the solder alloy 102 and lower than 100°C.

[0090] The bonding material 101 satisfying these conditions can provide a bonding material capable of forming a bonding portion having high heat resistance under the conditions of a low temperature of 100° C. and a short time of 10 minutes.

[0091] (Implementation method 2)

[0092] As the second embodiment, the influence of the metal composition of the solder alloy 102 was evaluated.

[0093] In order to confirm the effect of the second embodiment, as Examples 2-1 to 2-10 and Comparative Examples 2-1 to 2-6, bonding materials 101 were prepared in which the metal composition of the solder alloy 102 and the mixing ratio of the solder alloy 102 and the metal nanoparticles 103 were changed. The conditions and evaluation results of the bonding materials 101 in Examples 2-1 to 2-10 and Comparative Examples 2-1 to 2-6 are shown in FIG. Figure 4 In Table 2.

[0094] The method for preparing the bonding material 101 , the bonding process, and the evaluation method are the same as those in the first and second embodiments.

[0095] according to Figure 4 In Table 2, if we focus on the metal composition of solder alloy 102, in Examples 2-1 to 2-8 where the Bi ratio is 55wt.% to 60wt.%, the protective film detachment evaluation, joining evaluation, joining state evaluation, and heat resistance evaluation are all "A". In addition, in Example 2-9 where the Bi ratio is 45wt.% and the weight ratio of metal nanoparticles is 50wt.%, the protective film detachment evaluation, joining evaluation, heat resistance evaluation, and joining state are all "A". In Example 2-10 where the Bi ratio is 45wt.% and the weight ratio of metal nanoparticles is 40wt.%, the protective film detachment evaluation, joining evaluation, and joining state evaluation are "A", and the heat resistance evaluation is "B". Examples 2-1 to 2-10 are all above the evaluation criteria.

[0096] On the other hand, in the case of Comparative Examples 2-1 to 2-4 in which the Bi ratio is as low as 15 wt.% and 35 wt.%, the heat resistance is "C" despite the lower melting point than the solder alloy 102 of Examples 2-1 to 2-10. This is considered to be because the ratio of Sn and In, which are components that form an intermetallic compound with Cu of the metal nanoparticles 103, in the solder alloy 102 is large, and therefore a large amount of Cu is required to completely form an intermetallic compound, and the metal nanoparticles are insufficient.

[0097] In the case of Comparative Examples 2-5 and 2-6 in which the Bi ratio was as high as 70 wt.%, the bonding was "C". This is probably because the liquidus temperature increased with the increase in the Bi ratio, and therefore the alloy was not sufficiently melted at 100°C.

[0098] The following conclusions can be confirmed from the results of the second embodiment.

[0099] The composition of solder alloy 102 requires a Bi ratio of 45 to 60 wt.%, and particularly preferably 55 to 60 wt.%. Among them, Sn-55 wt.% Bi-20 wt.% In is most preferred because the permissible range of the weight ratio of metal nanoparticles is wide and the content ratio of expensive In is small.

[0100] In the bonding material 101 satisfying these conditions, a bonding material capable of forming a bonding portion having high bonding strength can be provided.

[0101] <Preferable conditions of the present invention>

[0102] As described above, according to the results of the first and second embodiments, as suitable conditions for demonstrating the effect of the bonding material of the present invention, the bonding material 101 only needs to include: a solder alloy 102 having a median particle size D50 of 100 nm to 2000 nm, composed of Sn, Bi, In and other inevitable components, and having a melting point of 100°C or less; metal nanoparticles 103 having a median particle size D50 of 50 to 500 nm and being Cu nanoparticles capable of forming an intermetallic compound with Sn and In contained in the solder alloy 102; and a solder flux 105. In addition, the metal nanoparticles 103 may have a protective film 104 on the surface that is detached at a temperature higher than the melting point of the solder alloy 102 and lower than 100°C. In addition, the weight ratio of the solder alloy 102 to the metal nanoparticles 103 is preferably a ratio in which all of the Sn and In contained in the solder alloy 102 become compounds with the metal nanoparticles 103 in the equilibrium diagram.

[0103] More preferably, the composition of the solder alloy 102 is preferably Sn-55wt.%Bi-20wt.%In.

[0104] More preferably, the weight ratio of the metal nanoparticles 103 to the total of the solder alloy 102 and the metal nanoparticles 103 is preferably 30 to 50 wt.%, more preferably 37.5 to 50 wt.%, and most preferably 40 to 50 wt.%.

[0105] Furthermore, the protective film 104 is preferably a straight-chain carboxylic acid having 4 to 8 carbon atoms.

[0106] In addition, the bonding structure is a bonding structure having an electronic component having a first electrode, a circuit substrate having a second electrode, and a bonding layer. In the bonding structure, the first electrode and the second electrode are bonded by the bonding layer, and the bonding layer is connected between the first electrode and the second electrode using an intermetallic compound composed of two or more elements of Cu, Sn, and In, and has a Bi-containing portion in an island shape in a matrix of the intermetallic compound.

[0107] In addition, the ratio of Bi may be 40 to 45 vol.%.

[0108] It should be noted that in this embodiment, the electrodes of the Si element used in the evaluation are Ti / Ni / Au, but the present application is not limited thereto, and the effects of the present application can be demonstrated as long as the electrodes can be joined using the solder alloy 102 .

[0109] In addition, in this embodiment, a Cu plate is used for bonding, but the present application is not limited to this. As long as the material is an electrode that can be bonded using the solder alloy 102 and can withstand 100°C as a temperature of the bonding process, the effect of the present application can be manifested.

[0110] It should be noted that the present application includes the case where any of the various embodiments and / or examples described above are appropriately combined to exert the effects of the various embodiments and / or examples.

[0111] Industrial Applicability

[0112] According to the bonding material and bonding structure of the present application, it is possible to provide a bonding material and bonding structure that can exhibit high heat resistance under low temperature and short-time heating, and can be used with a resin with low heat resistance as a base material in printable electronic technology, etc.

[0113] Description of Reference Numerals

[0114] 101 Joining material, 102 Solder alloy, 103 Metal nanoparticles, 104 Protective film, 105 Flux, 106 Joining structure, 107 First electrode, 108 Electronic component, 109 Second electrode, 110 Circuit board, 111 Joining layer, 112 Intermetallic compound, 113 Bi-containing portion.

Claims

1. A bonding material comprising: Solder alloy, wherein the average particle size D50 is 100nm to 2000nm, composed of Sn, Bi, In and other inevitable components, and the melting point is below 100°C; Metal nanoparticles, which are Cu nanoparticles having a median particle size D50 of 50 nm to 500 nm; and Flux composition, The metal nanoparticles have a protective film on their surfaces that is detached at a temperature higher than the melting point of the solder alloy and lower than 100° C., The weight ratio of the solder alloy to the metal nanoparticles is a ratio at which all of Sn and In contained in the solder alloy form an intermetallic compound with the metal nanoparticles in an equilibrium diagram.

2. The bonding material according to claim 1, wherein The composition of the solder alloy is Sn-55wt.%Bi-20wt.%In.

3. The bonding material according to claim 1 or 2, wherein The weight ratio of the metal nanoparticles to the total weight of the solder alloy and the metal nanoparticles is 30 wt.% to 50 wt.%.

4. The bonding material according to claim 1 or 2, wherein The weight ratio of the metal nanoparticles to the total weight of the solder alloy and the metal nanoparticles is 37.5 wt.% to 50 wt.%.

5. The bonding material according to claim 1 or 2, wherein The weight ratio of the metal nanoparticles to the total weight of the solder alloy and the metal nanoparticles is 40 wt.% to 50 wt.%.

6. The bonding material according to claim 1 or 2, wherein The protective film is a straight-chain carboxylic acid having 4 to 8 carbon atoms.

7. A bonding structure comprising: an electronic component having a first electrode, a circuit substrate having a second electrode, and a bonding layer between the first electrode and the second electrode, The first electrode and the second electrode are bonded by the bonding layer. The bonding layer connects the first electrode and the second electrode using an intermetallic compound of Cu, Sn, and In. The Bi-containing portion is provided in an island shape in a matrix of an intermetallic compound composed of two or more elements among Cu, Sn, and In.

8. The joint structure according to claim 7, wherein: The Bi-containing portion is 40 vol.% to 45 vol.%.